Study How People Are Ready To Be Infected with the Corona Virus (COVID-19) in Najaf Province/Iraq - Nadia Habeeb Sarhan; Zainab Abdullah Waheed (Indian Journal of Forensic Medicine & Toxicology, 2021)
The current study was designed to investigate some variables that affect the individual’s readiness to contractcoronavirus (COVID-19) for a specific sample in the Najaf governorate. About 70 cases have participatedin the questionnaire that was put on social media for the period from (1 March 2020) to (1 May 2020) ofthe population of the Najafi community – Iraq. The ages ranged between (16-70) years. The overall resultsobtained in this study showed that a group of variables showed a high willingness in the individual tocontract Coronavirus, such as not taking vitamins, zinc, and complementary minerals and less exposure tothe sun to support the immune system at a rate of (58.57%), The use of surgical masks instead of masks N95and the use of Dettol at a high rate when studying the study to get rid of the virus and eliminate it by ratios(88.57%, 47.14%) respectively At a probability level (P < 0.05 ). In addition, there was a lack of awarenessof preventive methods, such as continuing to wash hands with soap and water in the proportion (8.57%)of the total sample. Use of tissue during sneezing in the public, with average proportions (37.14%) withthe participation of samples from most of the Residential neighborhoods in Najaf. The results also showedthe variance of the mean value according to each axis which were, first axis (health activities), second axis(Commitment to prevention methods) and third axis (Commitment to instructions in light of the conditionsof society and instructions) with values of 2.12, 2.75 and 2.22, respectively, beside the relationship andconnection among them.